Método de apoio à formulação de estratégia de manutenção em ambiente industrial: um estudo de caso - Brand, Gustavo Gastmann (Universidade do Vale do Rio dos Sinos, 2011)
The main objective of this study is to show a method for implementation of Reliability Centered Maintenance (RCM) in a plating line of aluminum cylinders. For the analysis, It was used the time to failure and time to repair in the modeling. The work was developed from a case study and applied in a multinational manufacturer of internal combustion engines, whose production of aluminum cylinders achieves annual volume of 4.5 million pieces. Regarding the secondary objectives of this work, It´s mentioned the review of the literature on the concepts, history and maintenance applications, the concept of reliability, probability distribution models, parameter estimation, testing, adherence and reasons for failure. The main steps for implementing the method are: definition and system selection object of the study, functional analysis of failures; selection of critical items, collection and analysis of failure data, selection of maintenance actions, and determining maintenance intervals. As the Mean Time To Repair (MTTR) was very low compared to the Mean Time Between Failure (MTBF), the whole focus was to increase MTBF and not reduce MTTR. The result was the strategy of Preventive Maintenance, as predominant in many cases, associated with Predictive. The final consideration line maintenance strategies with production strategies for the system studied.
Keywords: Manutenção Centrada em Confiabilidade; Manutenção industrial; Estratégias de manutenção; Reliability centered maintenance; Industrial maintenance; Maintenance strategies; ACCNPQ::Engenharias::Engenharia de Produção